The impact of government debt on Malaysia's economic growth / Shaliza Azreen Mohd Zulkifli... [et al.] - Mohd Zulkifli, Shaliza Azreen; Abd Karim, Izzatul Syazwani; Sheikh Zain, Rozihanim; Chen, Jen Eem (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
The Malaysian economic situation has not been improving since the 2010 world economic crisis. The vulnerability of Malaysia government to accumulating high debt is rather worrisome. This study attempts to identify the factors affecting Malaysia's economic growth; namely foreign debt, domestic debt, labor force, trade openness and savings as independent variables and to identify the existence of a bi-directional relationship between economic growth and government debt. Annual time series data over the period from 1987 to 2017 was analyzed using the Dynamic Ordinary Least Square approach. It was found that domestic debt has a positive and significant impact on economic growth. On the other hand, foreign debt has a negative and significant effect on economic growth. Other than that, there is no existence of a bi-directional relationship between economic growth and government debt. This study provides insights for policymakers and investors about the importance of better and quality debt management. Theoretically, it provides a fresh view of the literature that will promote more empirical research in the future. Future studies should extend the current study by considering other key factors that might significantly influence the level of economic growth